Queer Teachers Negotiating Geographies of Safety in the 1990s - Mayernick, Jason (Historia y Memoria de la Educación, 2023)
This study demonstrates how three queer teachers in conservative spaces created geographies of safety during the 1990s. Each of the three teachers discussed initiated a geography of safety, and these histories are relevant to the ongoing negotiation that queer elementary and secondary educators today engage as they reconcile their moral authority as teachers with their gender(s) and sexualities.